The Influence of Work Motivation on Job Performance: Engagement and Burnout as Mediators - Zeng, Jing; Pathak, Shubham; Zhaowen, Shuai (Emerging Science Journal, 2025)
Based on self-determination theory, a conceptual model is proposed in which work motivation operates as the antecedent variable, with work engagement and occupational exhaustion acting as dual mediators. To test this framework, data were collected through a structured questionnaire from 469 academic staff members across 24 private higher education colleges in Jiangxi Province and analyzed using structural equation modeling (SEM). The results demonstrate that greater levels of educators' work motivation are significantly correlated with improved job performance and that this effect is channeled through increased work engagement and reduced burnout. By elucidating these mediatory pathways, the findings deepen theoretical comprehension of how motivation drives performance and yield practical guidance for devising effective motivation and performance-management strategies within private higher education institutions.